Genetic types of oils in Krasnodarsk region (Russia) - Goncharov I. V. Ivan Vasilyevich; Oblasov N. V.; Samoylenko V. V.; Fadeeva S. V.; Gayduk V. V.; Proshlyakov S. L.; Suslova E. U. (2009, 2009)
В фонде НТБ ТПУ отсутствует